The Outlaw. - Hughes, Howard; Hawks, Howard; Buetel, Jack; Mitchell, Thomas; Russell, Jane
Western legends Pat Garrett, Doc Holliday and Billy the Kid are played against each other over the law and the attentions of vivacious country vixen Rio McDonald.